An interesting result of a qualitative research: Academic exhaustion barrier to professionalism in medical students - Zohrehsadat Mirmoghtadaie; Soleiman Ahmady; Noushin Kohan; Tayebeh Rakhshani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Professionalism is an important measure of the efficacy of the medical education. Some studies showed that dominant values changed during clinical education, and some negative values might replace positive ones. In this regard, this study aimed to explore barrier to professionalism in clinical medical education. METHODS: This was a qualitative study conducted with the content analysis method. A total of 34 interviews with 23 participants were done. RESULTS: Two hundred forty-eight original codes were extracted from the research data, which were classified under the theme of "Academic Exhaustion" and the four following categories: "stressful environment, "human conflict," "Poor Inter professional collaboration," and "emotional exhaustion." DISCUSSION: It can be admitted that having full knowledge of the factors influencing professionalism from the viewpoint of stakeholders can improve the environmental and organizational conditions to prevent professional misconduct.